STRATEGI PENINGKATAN KUALITAS KELEMBAGAAN KOPERASI KABUPATEN KUANTAN SINGINGI - Lesty Ocky Suriana Lumban Turuan; Zaili Rusli Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Based in Kuantan Singingi Regency by focusing on the field of cooperatives. The Office of Cooperatives, UMKM, Trade and Industry of Kuantan Singingi Regency certainly has a strategy to make cooperatives in Kuantan Singingi Regency continue to grow and develop. The purpose of this study is to find out and analyze the strategy program and strategy formulation carried out by the Department of Cooperatives, UMKM, Trade and Industry of Kuantan Singingi Regency. The theoretical concept used as an indicator of strategy performance in improving institutional quality by the Office of Cooperatives, UMKM, Trade and Industry of Kuantan Singingi Regency is the theory of Hubeis and Najib dalam (Dian, 2017), namely: Annual goal setting, Policy formulation, Motivating workers, Allocating resources , and for discussion of strategies using the theory of SWOT Analysis (Strengths, Weaknesses, Opportunities and Threats). This study uses a snowball sampling technique with data collection techniques including: observation, interviews, literature study and documentation. The results of this study indicate that the strategy of the Office of Cooperatives, UMKM, Trade and Industry of Kuantan Singingi Regency in improving institutional quality is on target, with the SWOT analysis producing a Recommendation the strategy given is Progressive, meaning that the organization is in prime and steady condition so it is possible to continue expand, increase growth and achieve maximum progress. This situation is very beneficial, because the strength possessed can be utilized for the opportunities that exist.Keywords : Strategy, Instutional Quality, Cooperatives